2019
DOI: 10.1021/acs.jpcb.9b10432
|View full text |Cite
|
Sign up to set email alerts
|

Competing Interactions: Evolution of Inter and Intramolecular Hydrogen Bonds in Salicylic Acid at High Pressures

Abstract: Benzoic acid derivatives are important molecular systems in the pharmaceutical industry. Salicylic acid is distinct among the derivatives of benzoic acid due to the presence of an intramolecular hydrogen bond. With a view to study the evolution of inter and intramolecular hydrogen bonding at shorter length scales, in situ high pressure Raman spectroscopic measurements, angle dispersive X-ray diffraction experiments, and density functional theory (DFT) based first principle calculations have been carried out on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The relative Gibbs free energies (▵ G ) hint that the latter, in which the hydroxyl points toward the carbonyl of the carboxylic acid, is 3.64 kcal/mol more stable than the alternative trans ‐configuration 1. This finding agrees with the crystal structure of salicylic acid [51] . The same HB pattern is systematically applied for all designed models for neutral cis and trans prodrugs.…”
Section: Resultssupporting
confidence: 80%
“…The relative Gibbs free energies (▵ G ) hint that the latter, in which the hydroxyl points toward the carbonyl of the carboxylic acid, is 3.64 kcal/mol more stable than the alternative trans ‐configuration 1. This finding agrees with the crystal structure of salicylic acid [51] . The same HB pattern is systematically applied for all designed models for neutral cis and trans prodrugs.…”
Section: Resultssupporting
confidence: 80%
“…The results revealed that site P plays a critical role in enzymatic activity and specificity. As SA forms an intramolecular hydrogen bond between the carboxyl and the ortho hydroxyl groups [49], SA conformation probably hinders the rotation of the benzene ring within the OsSAH active pockets. Therefore, the ratio of 3-to 5-hydroxyl products was determined when the substrate was initially associated with the OsSAH enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The final optimized and equilibrated structures at each temperature were used for MD simulation under external shear forces to investigate molecular reorientation and shear-induced molecular interactions ( 103 105 ). Shear rates of 1, 0.1, 0.01, 0.001, 0.0001, and 0.00001 ps −1 were applied to each mixture model at the upper facet under the NPT ensemble for a period of 1,000 ps ( 106 108 ).…”
Section: Computational Detailsmentioning
confidence: 99%